SISTEM PENJUALAN TIKET PADA KAWASAN KONSERVASI BERBASIS WEBSITE (STUDI KASUS: KAWASAN KONSERVASI, INDONESIA) - Yulian Pamungkas; Eka Budhy Prasetya; Rita Dewi Risanty (Tekinfo: Jurnal Bidang Teknik Industri dan Teknik Informatika, 2022)
Website e-commerce, also known as electronic commerce or online commerce, refers to the purchasing and selling of products and services via websites on the internet, as well as the transmission of money and data required to complete these transactions. There are many conservation areas in Indonesia, both on land and at sea, where payment system procedures, buying admission tickets, and providing information about current conservation areas are still done in the traditional way, namely Conservation Areas in managing and recapitulating income finances. sales to organizations or residents in the vicinity of conservation areas in a transparent manner while continuing to keep paper records, making them less effective and efficient. Tourists also have no idea how many quotas are available. As a result, if visitors visit the conservation area and the quota is not available, they will be unable to access. And then there's the news - whether it's true or not, news that casts doubt on the Conservation Area. Based on the challenge, a waterfall technique was used to create an Application for Making a Website-Based Automatic Conservation Area Ticket Sales System, which included analysis, design, program code, program testing, and program implementation. The application's results show that it can assist Conservation Areas and tourists in managing and recapping money more effectively and efficiently, and that tourists can read information directly provided by Conservation Areas as well as the amount of available quotas Keywords: Application, E-commerce, Conservation Area, Indonesia, Website, Waterfall